The International Lender of Last Resort : How Large is Large Enought? - Jeanne, Olivier (Washington, D.C. : International Monetary Fund, 2001)
This paper considers how an international lender of last resort (LOLR) can prevent self-fulfilling banking and currency crises in emerging economies. We compare two different arrangements: one in which the international LOLR injects liquidity into international financial markets, and one in which its resources are used to back domestic banking safety nets. Both arrangements would require important changes in the global financial architecture: the first one would require a global central bank issuing an international currency, while the second one would have to be operated by an "international banking fund" closely involved in the supervision of domestic banking systems.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet